A review on industrial automation system - Madala, Kranthi; K.V. Daya Sagar, Dr (International Journal of Engineering and Technology, 2018)
The prospect to build robust industrial systems & applications in the field of RFID, mobile &sensor devices, wireless, Internet of Things (IOT) has been provided. In very modern years many IOT applications have been increasingly developed and deployed. In our day to day life controlling and monitoring plays a major role now a days. Using advanced technologies we can monitor and control everything. Be-cause of high speed internet a wonderful feature that came into picture is Remote access. The main objective of this proposed system is for those who are away from their industry and want to control devices by providing technology oriented and low cost system. Â Â